2019
DOI: 10.1039/c9cc01249d
|View full text |Cite
|
Sign up to set email alerts
|

Design and reactivity of pentapyridyl metal complexes for ammonia oxidation

Abstract: Computational and experimental work shows that Mo pentapyridal complexes can oxidize ammonia in the presence of a chemical mediator and evolve N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 36 publications
4
63
1
Order By: Relevance
“…[29][30][31][32][33] Bullock and coworkers recently reported a detailed theoretical investigation using the PY5 ligand platform 34,35 for AO with M = Cr, Mo, W, Mn, Fe, Ru, Os. 36 They observed that the [PY5]Fe(II) complex behaved quite differently to the rest of the metals Please do not adjust margins Please do not adjust margins investigated, notably due to the significant radical character of the Fe-amido and Fe-imido intermediates computed. We therefore thought of using our tetrapodal dianionic pentadentate B 2 Pz 4 Py ligand platform, which has been successful at accessing a variety of first-row metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Bullock and coworkers recently reported a detailed theoretical investigation using the PY5 ligand platform 34,35 for AO with M = Cr, Mo, W, Mn, Fe, Ru, Os. 36 They observed that the [PY5]Fe(II) complex behaved quite differently to the rest of the metals Please do not adjust margins Please do not adjust margins investigated, notably due to the significant radical character of the Fe-amido and Fe-imido intermediates computed. We therefore thought of using our tetrapodal dianionic pentadentate B 2 Pz 4 Py ligand platform, which has been successful at accessing a variety of first-row metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Bullock and coworkers recently reported a detailed theoretical investigation using the PY5 ligand platform [34][35] for AO with M = Cr, Mo, W, Mn, Fe, Ru, Os. 36 They observed that the [PY5]Fe(II) complex behaved quite differently to the rest of the metals investigated, notably due to the significant radical character of the Fe-amido and Fe-imido intermediates computed. We therefore thought of using our tetrapodal dianionic pentadentate B2Pz4Py ligand platform, which has been successful at accessing a variety of first-row metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Welldefined molecular model systems are amenable to detailed mechanistic interrogation, and their study in this context is expanding rapidly. Stoichiometric ammonia oxidation (AO) to N2 has been demonstrated for transition metal complexes of Mo, 3 Mn, 4 Os, 5 and Ru. 6,7 More recently, AO catalysis has been reported using Ru 8 and Fe 9 complexes under chemical and electrochemical conditions.…”
Section: Introductionmentioning
confidence: 99%